Influence of Y doping on catalytic activity of CeO2, MnOx, and CeMnOx catalysts for selective catalytic reduction of NO by NH3 - La Greca, Eleonora; Kharlamova, Tamara S.; Grabchenko, Maria V.; Svetlichnyi, Valerii A.; Pantaleo, Giuseppe; Consentino, Luca; Stonkus, Olga A.; Vodyankina, Olga V.; Liotta, Leonarda Francesca (Catalysts)
Novel yttrium-doped CeO2, MnOx, and CeMnOx composites are investigated as catalysts for low-temperature NH3-SCR. The study involves the preparation of unmodified oxide supports using a citrate method followed by modification with Y (2 wt.%) using two approaches, including the one-pot citrate method and incipient wetness impregnation of undoped oxides. The NH3-SCR reaction is studied in a fixed-bed quartz reactor to test the ability of the prepared catalysts in NO reduction. The gas reaction mixture consists of 800 ppm NO, 800 ppm NH3, 10 vol.% O2, and He as a balance gas at a WHSV of 25,000 mL g−1 h−1. The results indicate that undoped CeMnOx mixed oxide exhibits significantly higher deNOx performance compared with undoped and Y-doped MnOx and CeO2 catalysts. Indeed, yttrium presence in CeMnOx promotes the competitive NH3-SCO reaction, reducing the amount of NH3 available for NO reduction and lowering the catalyst activity. Furthermore, the physical-chemical properties of the prepared catalysts are studied using nitrogen adsorption/desorption, XRD, Raman spectroscopy, temperature-programmed reduction with hydrogen, and temperature-programmed desorption of ammonia. This study presents a promising approach to enhancing the performance of NH3-SCR catalysts at low temperatures that can have significant implications for reducing NO emissions.